Optimization of Turnover Through Digital Marketing Training for Fisherman Products in Desa Pasar Sorkam District Sorkam Barat Regency Tapanuli Tengah - Silalahi , Amlys Syahputra; Hutagalung, Bongsu; Lubis, Andrew; Putra, Adika Fajar (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Desa Pasar Sorkam is about 34 km from Sibolga City, and 45 km from the capital of Central Tapanuli Regency, Pandan. So far, Sorkam District has been divided into two regions, namely West Sorkam District. Pasar Sorkam Village consists of 5 hamlets and has been led by 13 previous Village Heads. The people of Pasar Sorkam Village come from various tribes and regions, namely Bataak, Java, Nias, and Padang. The majority of the people of Pasar Sorkam Village have a livelihood as fishermen who have been awarded and depend on the sea conditions that lie wide and only a small part work as farmers. The problems faced by farmers and fishermen in Pasar Sorkam village are that the utilization of fishermen's products is not optimal due to limitations regarding the use of technology such as digital marketing. So that the development of the handling of processed marine products is still running slowly and is still not in line with expectations. It is hoped that this service will be able to realize the optimization of turnover through digital marketing training for the results of fishermen's products in the Desa Pasar Sorkam, sub-district. Sorkam Barat Districts Tapanuli Tengah.